2015
DOI: 10.4314/ahs.v15i3.38
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between soil cobalt and vitamin B12 levels in the liver of livestock in Saudi Arabia: role of competing elements in soils

Abstract: Results: Our results indicated that the levels of Co in surface soil (0-15 cm) were higher than in sub-surface soil (>15 cm-45 cm). In contrast, Pb and Zn were higher in sub-surface soil than in surface soil. A significant positive correlation existed between the levels of Co and vitamin B 12 in the liver of livestock. However, Co was not detected in muscle tissues while vitamin B 12 was present at very low levels in comparison with the levels found in the liver. The results indicated that Zn 2+ , Pb 2+ compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Interestingly to note, that Co was detected in 12 bee pollen samples out of 15, while other bee product samples did not reveal this element. Studies published in literature have shown that content of Co correlates with amount of vitamin B12 [49]. Evaluation of vitamin B12 was not under scope of this study, but there is a high chance that bee pollen may have higher content of vitamin B12 compared to other bee products, as cobalt is a key element in the structure of vitamin B12 (cyanocobalamin).…”
Section: Mineral Content In the Tested Samplesmentioning
confidence: 99%
“…Interestingly to note, that Co was detected in 12 bee pollen samples out of 15, while other bee product samples did not reveal this element. Studies published in literature have shown that content of Co correlates with amount of vitamin B12 [49]. Evaluation of vitamin B12 was not under scope of this study, but there is a high chance that bee pollen may have higher content of vitamin B12 compared to other bee products, as cobalt is a key element in the structure of vitamin B12 (cyanocobalamin).…”
Section: Mineral Content In the Tested Samplesmentioning
confidence: 99%
“…Concentration of Ni in this study was observed at 3.03 ppm. Co is required in trace quantity for human body and is a key constituent of cobalamin known as Vitamin B 12 [39]. The concentration of Co in the present study was observed at 0.33 ppm, and WHO has not established yet permissible limits for Co in medicinal plants.…”
Section: Icp-msmentioning
confidence: 51%
“…This is likely due to increased levels of cobalt present in the concentrate used in the TMR ration and in the root nodules of the CLV sward. Leguminous plants such as Trifolium repens L. exhibit a high affinity for the concentration of cobalt [70], which is required by nitrogen-fixing microflora present in the root nodule [71] and forms the central constituent in cobalamin synthesis [72]. The lower concentrations observed in GRS-derived SMP may therefore be due to the absence of cobalt from the leaves of the perennial ryegrass exclusively consumed by the cows assigned to this feeding system.…”
Section: Vitamin B12 (Cobalamin)mentioning
confidence: 99%